Social Networks and Local Collaboration in Natural Resources Management in Developing Countries: A Review of the Theoretical and Empirical Literature (Tanzania Journal for Population studies and Development, 2017)
While there has been a growth of literature in the area of social networks and natural resources management (NRM), the theoretical and empirical literature on social network dynamics of local collaboration in NRM in developing countries, and Africain particular, remains underdeveloped. This paper reviews the theoretical and empirical literature of social networks and local collaboration in NRM, and develops a conceptual framework for examining social network dynamics of local collaborationin NRM. Its discussion centres on considerations for applying a stochastic actor-based modelling approach of network dynamics, which offers one of the several noteworthy approaches to social network analysis. The paper concludes that understanding themechanisms that underpin the dynamic nature of social networks and local collaboration in NRM helps in developing appropriate policies that encourage collaborative efforts, and foster local commitment to sustainable NRM.